The newspaper «Gazak Adebieti» and the problem of term formation (Herald of Journalism, 2020)
In the article the Kazakh press, especially the newspaper «Kazakh lit- erature» as one of the masscirculated publications which are of great politi- cal importance, its role in formation of terms are considered. In the article some often used terms are given in concrete examples. It is impossible   to tell that all these terms are successfully formed, it is defined that some terms are given in several variants. An attempt to define the methods of formation of the terms used on pages of the newspaper is made.
Keywords: the term, the Kazakh terminology, terms in the languages of the nation, new names, the use of words, wordstock, the Kazakh press, to use paralelly.